One hundred new records, a new species, and the first pictures of Agonocryptus Cushman (Hymenoptera, Ichneumonidae, Cryptinae) - Supeleto, Fernanda A.; Aguiar, Alexandre P. (Zootaxa, 2022)
Updated distribution maps are provided for all known species of Agonocryptus, with 115 new distribution records for 16 species, an expansion from 166 to 281 unique coordinates, or nearly 70%, in relation to what was previously published. A new species is proposed, A. glaphyrus sp. nov., from Colombia. All taxa previously treated as subspecies are raised to the rank of species, as follows: A. chichimecus (Cresson, 1873) stat. nov., A. coxinota Gupta, 1982 stat. nov., A. discoidaloides (Viereck, 1905) stat. nov., A. flavosternum Gupta, 1982 stat. nov., A. nigrifemur Gupta, 1982 stat. nov., A. nigristernum Gupta, 1982 stat. nov., A. paulus Gupta, 1982 stat. nov., and A. tucumanus Gupta, 1982 stat. nov. New distribution data is provided for the following taxa, with new records for countries specified where applicable: A. adustus Gupta, 1982, new to Colombia; A. argentinus Gupta, 1982; A. brevicauda Kasparyan & Ruíz-Cancino, 2005, new to Brazil; A. chichimecus; A. discoidaloides; A. flavosternum; A. fumosus Gupta, 1982; A. heathi (Brues, 1912); A. lioneli Gupta, 1982; A. nigristernum; A. physocnemis (Brullé, 1846); A. rufithorax Gupta, 1982; A. rugifrons Gupta, 1982; A. russulus Gupta, 1982; A. tricolor Gupta, 1982; and A. varus (Brullé, 1846), new to Bolivia, Brazil, Colombia, French Guyana, Guyana, and Trinidad & Tobago. Images of the studied species are published for the first time, including the males of A. discoidaloides, A. physocnemis, and A. rugifrons, documenting both the typical morphology of each taxon and their morphological variation, which is also described and discussed. Specimens cited by Gupta (1982) as likely to represent a distinct subspecies of A. varus are identified as Digonocryptus zopherus Aguiar & Santos, 2012. Elevation data, both from the literature and original, is compiled and compared, revealing a range of preferences among different species.